2014
DOI: 10.1190/int-2013-0154.1
|View full text |Cite
|
Sign up to set email alerts
|

mCSEM data interpretation for hydrocarbon exploration: A fast interpretation workflow for drilling decision

Abstract: In a hydrocarbon exploration workflow, marine controlled-source electromagnetic (mCSEM) data are usually acquired after seismic interpretation for prospect identification and close-to-the-drilling decision making. Therefore, the mCSEM interpreter must provide quick answers to the asset teams in a way that the EM interpretation can add value to that decision. To achieve that goal, Petrobras developed a fast-track mCSEM interpretation workflow that consists in identifying anomalies in the mCSEM data set by frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
2
8
1
Order By: Relevance
“…This error can be reduced by constraining the responses using a priori information, for example from a well log, as the one exhibited in Figures 9 and 10. As the study shown here doesn't include any such a priori information, the results reproduce the common behavior, and the maximum resistivity in the resulting models is located at about 500 m above the peak values found in Buonora et al (2014).…”
Section: Real Datasupporting
confidence: 56%
See 4 more Smart Citations
“…This error can be reduced by constraining the responses using a priori information, for example from a well log, as the one exhibited in Figures 9 and 10. As the study shown here doesn't include any such a priori information, the results reproduce the common behavior, and the maximum resistivity in the resulting models is located at about 500 m above the peak values found in Buonora et al (2014).…”
Section: Real Datasupporting
confidence: 56%
“…2-Above 4000 m, the curves show a strong indication of a resistive zone, approximately in the correct depth as indicated by Buonora et al (2014). Whereas in the previous results this resistive regions can be interpreted as being composed of two distinct zones, in our results only the horizontal resistivity curve of the global smoothness inversion shows any indication of such division.…”
Section: Real Datacontrasting
confidence: 52%
See 3 more Smart Citations